Nearshore Larval Retention and Cross-Shelf Migration of Benthic Crustaceans at an Upwelling Center - Morgan, Steven G.; Miller, Seth H.; Robart, Matt J.; Largier, John L. (Frontiers in Marine Science, 2018)
Planktonic larvae are considered to be highly susceptible to offshore transport in productive upwelling regions, thereby increasing dispersal and limiting recruitment. However, larvae of 42 species of nearshore benthic crustaceans primarily developed on the inner shelf at locations both in (98.5%) and away (99.8%) from a perennial upwelling center during the peak upwelling season in a recruitment-limited region characterized by strong, persistent upwelling. During three cross-shelf cruises conducted at each location, larvae of 21 species remained on the inner shelf at both sites by occurring below a shallow Ekman layer of seaward-flowing surface waters throughout development while larvae of the other species migrated to mid-shelf (four species) or offshore (14 species) by occurring closer to the surface early in development. Postlarvae apparently returned to adult habitats inshore either by descending to landward-flowing upwelled waters or ascending to the surface where behavior allows them to be transported shoreward by internal waves, diel wind cycles or wind relaxation events. Thus, the cause of recruitment limitation along upwelling coasts does not appear to be due to losses from offshore transport, requiring new research directions to advance our understanding of population dynamics, structure and connectivity.